Photochromism of novel [1]benzothien-2-yl fulgides. Issue 38 (22nd September 2016) - Zmeeva, Sofiya Yu.; Rybalkin, Vladimir P.; Popova, Lidiya L.; Tkachev, Valerii V.; Revinskii, Yurii V.; Tikhomirova, Karina S.; Starikov, Andrey G.; Dubonosov, Alexander D.; Bren, Vladimir A.; Aldoshin, Sergey M.; Minkin, Vladimir I.
Abstract: Novel [1]benzothien-2-yl fulgides were synthesized and their structures established based on analysis by 1 H, 13 C NMR and IR spectroscopy, mass-spectrometry and X-ray diffraction. All the compounds exist in the ring-opened Z- isomeric forms. Under UV-irradiation fulgides with no substituent at the methylidene bridge undergo thermally or photochemically reversible Z/E -photoisomerization, but do not convert to the cyclic isomeric forms. Under the same conditions, 3-(1-(3-methyl[1]benzothien-2-yl)ethylidene)-4-(1-methylethylidene)-dihydrofuran-2, 5-dione with a methyl group at the methylidene bridge rearranges into the thermally stable colored 1, 3-cyclohexadiene ring-closed isomer which possesses improved spectral characteristics as compared with 2-thienyl and [1]benzothien-3-yl analogues. Irradiation with visible light results in the fast backward isomerization into the initial colorless hexatriene ring-opened form. Graphical abstract: Novel [1]benzothien-2-yl fulgides have been synthesized. Under irradiation the compounds with R 1 =H undergo reversible Z/E -photoisomerization, the compound with a methyl group ( R 1 =Me) at the methylidene bridge rearranges into the thermally stable colored ring-closed isomer.